RANCANG BANGUN SISTEM INFORMASI DISTRIBUSI LOGISTIK BERBASIS WEB PADA PT. LUGAS - Putri, Sekar; Sudarsono , Bernadus Gunawan; Syahriyanto, Syahriyanto (LPPM Universitas Bina Bangsa, 2024)
PT. Lugas is a security services company founded on May 21, 2008 by instructors who are experienced in the field of security and protection. In 2021, PT. Lugas developed his business by switching to logistics services, handling export and imports, opening domestic shipping routes. Problem that occurs at PT. Lugas is where there is no processing of goods distribution data, it is difficult to make shipping and receiving reports, and there is no availability of an integrated system via website, resulting in employee performance processes and logistic distribution activities not running well. From the existing problems, a web-based logistics distribution information system was designed and built which is expected to be able to solve the existing problems. In defining needs and analyzing system development, data collection methods were carried out by means of observation, interviews and literature studies from various sources of information. The analysis and design method uses Unified Modelling Language (UML), a logistics distribution system at PT. Lugas using the PHP programming language and database using MySQL database